CREATIVE STRATEGY OF PROGRAM DIRECTOR AT 4 CITIES WAYANG BEBER VICOLMING SHOW - Ranangsari, Kosalalita Anggiyumna; Fenda, Intan Yulia Febbyu (Seni Media Rekam ISI Surakarta, 2020)
The Covid-19 pandemic was responded to by the wayang beber art group quickly and creatively. They held shows wayang beber in 4 cities by utilizing video conferencing & live streaming (Vicolming). The new technology used for the performances of 4 remote puppeteers (dalang) was a challenge for the program director. This research is intended to explore the strategy of the program director in producing the 4 cities wayang beber Vicolming show. This study used qualitative descriptive research. The data collection used the interview and documentation methods, while the data analysis used the Interactive Analysis model. The result of this study is that the program director applies a strict strategy at the pre-production, production and post-production stages in this wayang beber Vicolming show. Creative strategies in pre-production include determining the topic of Covid-19; and the Video Conference & Live Streaming technology used, the preparation of video, audio and internet equipment for each art group in 4 cities; determination of the ideal schedule and duration, and live streaming rehearsals. The strategy at the production stage included: 1) The strategy of arranging a dalang's performance from one puppeteer to another is related to the quality of the image and sound as well as the internet connection, so that the rundown changed a lot; 2) Taking pictures is done limitedly, because the equipment between the puppeteers is different; The post-production stage strategy focused on preparing live streaming videos uploaded to the Youtube channel.